ANALYSIS AND POTENTIAL THE ECO-ENZYME OF SEVERAL TYPES OF FRUIT PEELS IN LEACHATE REMEDIATION - Rasyidah; Nasution, Rizki Amelia (BRIN - Badan Riset dan Inovasi Nasional, 2024)
This research aims to determine the potential of ecoenzymes from several types of fruit peel in the process of reducing TDS levels of COD, BOD, ammonium and phosphate as well as the number of bacterial colonies in leachate water. So the research involved activities to make ecoenzymes from 4 types of fruit peel, namely banana, dragon fruit, pineapple and orange. Next, the ecoenzyme results were applied to leachate water to test its remediation potential in a ratio of 1:2 (10% ecoenzyme). This research uses a descriptive method, which uses parameters namely TDS, COD, BOD, phosphate, ammonium, and counting bacterial colonies. The results show that ecoenzymes have the potential to remediate leachate waste during five days of incubation, where it can be seen that ecoenzymes can reduce ammonium and phosphate levels but not BOD and COD. From the results, the average reduction in ammonia levels was higher for ecoenzymes from banana peel and pineapple fruit with an average value (mg/l) of P1=14.6; P2=0.55; P3=1.44; P4=0.675 and P5=2.44 (P1: Leachate; P2: Leachate + banana peel ecoenzyme; P3: Leachate + Dragon Fruit peel ecoenzyme; P4: Leachate + Pineapple Peel; P5: Leachate + Fruit peel Orange). Meanwhile, the highest reduction in phosphate was found in remediation using ecoenzymes from orange peel where the average value was P5=3.05 < P1=8.2. The results of ecoenzyme remediation from four types of fruit peel only have the potential to reduce ammonia levels, and likewise the reduction in phosphate occurs after adding orange peel ecoenzymes.